2020
DOI: 10.1002/cti2.1189
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and isotype assessment of antibodies targeting the spike protein receptor‐binding domain of severe acute respiratory syndrome‐coronavirus‐2 in COVID‐19 patients as a function of age, biological sex and disease severity

Abstract: Objectives. There is an incomplete understanding of the host humoral immune response to severe acute respiratory syndrome (SARS)-coronavirus (CoV)-2, which underlies COVID-19, during acute infection. Host factors such as age and sex as well as the kinetics and functionality of antibody responses are important factors to consider as vaccine development proceeds. The receptorbinding domain of the CoV spike (RBD-S) protein mediates host cell binding and infection and is a major target for vaccine design to elicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 51 publications
8
34
1
1
Order By: Relevance
“…After the cohort (n = 8697) had been corrected for underrepresentation of the greater than 65 years age group, the marked increase in SARS‐CoV‐2 IgG levels that was observed with advancing donor age was similar for both sexes, except for the 50–55 years age group, where a trend for higher index S/C values was seen for plasma from male versus female donors (Figure 3(A)). Although higher fatality rates and severe COVID‐19 are consistently reported for men, 24 there was no significant difference in serum IgG levels across sex in mild COVID‐19, 25,26 fully consistent with the results obtained here. In a previous study, we reported significantly higher neutralization titer for CP units from male donors 17 .…”
Section: Effect Of Plasma Donor Demographics On Sars‐cov‐2 Antibodiessupporting
confidence: 89%
“…After the cohort (n = 8697) had been corrected for underrepresentation of the greater than 65 years age group, the marked increase in SARS‐CoV‐2 IgG levels that was observed with advancing donor age was similar for both sexes, except for the 50–55 years age group, where a trend for higher index S/C values was seen for plasma from male versus female donors (Figure 3(A)). Although higher fatality rates and severe COVID‐19 are consistently reported for men, 24 there was no significant difference in serum IgG levels across sex in mild COVID‐19, 25,26 fully consistent with the results obtained here. In a previous study, we reported significantly higher neutralization titer for CP units from male donors 17 .…”
Section: Effect Of Plasma Donor Demographics On Sars‐cov‐2 Antibodiessupporting
confidence: 89%
“…In contrast, SARS-CoV-2-specific IgG was detected in a wide range of SARS-CoV-2-infected subjects, including those with mild, moderate and severe disease manifestations. Contrary to other studies [ 23 , 24 ], we did not see a significant difference between patients with mild or moderate and severe disease. The fact that OD values from a single dilution do not have a linear correlation with titers might contribute to the underestimation of the IgG response in patients with high levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, in severely diseased patients, we found a correlation of SARS-CoV-2-specific IgA1 and IgA2 levels with age. This observation is in accordance with other studies showing that increased age is associated with stronger disease [ 24 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Among 1847 participants working in three sites at an institution in Paris conurbation, of those detected immunoglobulin G (IgG)-positive for SARS-CoV-2 nucleocapsid (N)- and spike (S)-proteins, 21% had been asymptomatic [ 8 ]. Further evidence suggests that there is a positive correlation between the severity of clinical symptoms and serum levels of anti-SARS-CoV-2 antibodies, being less prominent in oligosymptomatic patients [ 9 , 10 ]. According to other reports, asymptomatic infection may not even induce a detectable humoral response, suggesting that high viral load is possibly associated with the levels of humoral immunity.…”
Section: Introductionmentioning
confidence: 99%